Collins primary dictionary - Goldsmith, Evelyn; Dann, Penny Lapage, Ginny (HarperCollins Children's Books London, 1995)
Part of a series of Collins Children's Dictionaries, this dictionary contains over 3000 alphabetically organized and defined words. Practical tips on how to use this first dictionary for children are included, as well as illustrations designed to entertain as well as inform the reader.